Investigation of proton damage in III-V semiconductors by optical spectroscopy - Yaccuzzi, Exequiel Eliseo (2016)
Fil: Yaccuzzi, Exequiel. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina